Bacteriocin-Producing Staphylococci and Mammaliicocci Strains for Agro-Food and Public Health Applications with Relevance of Micrococcin P1 - Rosa Fernández-Fernández; Carmen Lozano; Allelen Campaña-Burguet; Carmen González-Azcona; Tamara Álvarez-Gómez; Rocío Fernández-Pérez; Raquel Peña; Myriam Zarazaga; Jaime Carrasco; Carmen Torres (Antibiotics)
Antimicrobial-producing strains and their bacteriocins hold great promise for the control of bacterial diseases, being an attractive alternative to antibiotics. Thus, the aim of this study was to evaluate the inhibitory activity of 15 bacteriocin-producing staphylococci and mammaliicocci (BP-S/M) strains and their pre-purified extracts with butanol (BT) against a collection of 27 harmful or zoonotic strains (including Gram-positive/-negative bacteria and molds) with relevance in the public health and agro-food fields. These indicators (excluding Gram-negative strains) were grouped into seven categories based on their potential application areas: dairy livestock mastitis, avian pathogen zoonoses, swine zoonoses, food safety, aquaculture, wine making, and mushroom cultivation. In addition, cross-immunity assays between the BP-S/M strains were carried out to identify potential strain combinations to enhance their activity against pathogens. Finally, the hemolytic and gelatinase activities were tested in the BP-S/M strains. A strong inhibitory capacity of the BP-S/M strains was verified against relevant Gram-positive indicators, such as methicillin-resistant Staphylococcus aureus, Listeria monocytogenes, and Clostridium perfringens, among others, while no activity was detected against Gram-negative ones. Interestingly, several BT extracts inhibited the two mold indicators included in this study as representants of mushroom pathogens. The Micrococcin P1 producer Staphylococcus hominis C5835 (>60% of indicators were intensively inhibited by all the methods) can be proposed as a potential candidate for the control of bacterial diseases in the aforementioned categories alone or in combination with other BP-S/M strains (mainly with Staphylococcus warneri X2969). In this regard, five potential combinations of BP-S/M strains that enhanced their activity against specific pathogens were detected.